Smart Wifi Circuit Breaker - RAZIF, DANIEL (Progress in Engineering Application and Technology, 2023)
The primary concern of the end user is the possibility of a power outage, which would cut off the buildings' access to electricity. The ELCB has the drawback of not being able to return the power supply to normal operation after even a brief interruption. Some electric loads, such as refrigerators, aquariums, and alarm systems, require a continual supply of electricity to prevent malfunction or temperature changes, making power continuity vital for homeowners. When an ELCB issue is detected, mechanical switches trip the circuit breaker. When a trip happens, the user's main worry is turning on the distribution board (DB) manually. For this reason, the proposed project entails developing an automated system for resetting the ELCB. The ability to switch on after a trip and the need for constant standby close to the DB are also issues that will be addressed by this project. The servo motor in this project is controlled by an ESP32 microcontroller, which is also used to connect to the Internet of Things and retrieve real-time data from the power distribution board. After the user has reset the ELCB three times, a notification will be sent through the Blynk mobile application. When no one is home, this method provides a useful option for users. In order to prevent faults from damaging wire and appliances, the system is set up for three tries.Additionally, this technology provides the user with uninterrupted power and real-time monitoring.